1169 Innovative Exposure to Sleep Medicine for Medical Students. (27th May 2020) - Gupta, S; Golden, E; Howell, M; Irfan, M
Abstract: Introduction: Lack of exposure to the field of Sleep Medicine at the medical student level hinders sleep training. Instead of the traditional didactic style, there is a need for innovative collaborative measures to spark interest in the younger generation of learners. The goal of this educational endeavor was to introduce medical students to the field of Sleep Medicine through the platform of Student Interest Group in Neurology (SIGN). Methods: An interactive session was conducted for SIGN at the University of Minnesota. 24 second-year medical students were divided into 6 groups. The session consisted of introduction, videos of common sleep disorders and interactive briefing afterward. 5-point Likert scale pre and post-session surveys were administered to measure the level of knowledge regarding sleep, familiarity with diagnostic tools, available education, pathways to Sleep Medicine, learner's interest and impact of the session. Wilcoxon matched-pairs signed-rank test was performed to compare pre- and post-surveys. Results: There was a significant improvement in measures of students' knowledge about sleep diagnostic modalities (p =7.8*10 -5 ), education received (p= 3.2*10 -5 ) and pathways to sleep medicine (p=4.1*10 -5 ). Survey also showed improvement in students' interest in pursuing a Sleep Medicine career (p=0.07). There was no difference in knowledge about the importance of sleep for health (p=0.69). All of the students found the session to be informative. Conclusion: Early exposure to sleep disorders in interactive format was well received by the medical students with significant improvement in scores regarding sleep education, awareness of diagnostic modalities, career pathway and interest in sleep medicine (p=0.07). Integration of exposure to Sleep Medicine within the medical curriculum in an innovative format should be done to instigate interest in this field. Further larger studies are warranted to evaluate the changes in the students' interest in the subspecialty with an introduction in the early stages of their career. Support: